CAMPUR KODE PADA TEKS LAGU DALAM ALBUM CAN’T BUY MY LOVE OLEH YUI YOSHIOKA - SUNARIYANTI, YENI IIS (Jurnal Ilmiah Mahasiswa FIB, 2013)
Code mixing is the use of more than one language or code in a discourse although the pattern is not clearly understood. In the globalization era, Japan language has been influenced by the foreign culture. The example of this case is the code mixing of the texts of songs in Can’t Buy My Love Album. Problems in this research are (1) how is the form and type of code mixing in the text of Japan language songs in Can’t Buy My Love Album which are performed by Yui Yoshioka, and (2) how is the function of communication in the code mixing in the text of Japan language songs in Can’t Buy My Love Album which are performed by Yui Yoshioka. Research is qualitative descriptive. The objective of research is to obtain a descriptive view about code mixing in Japan song texts. Result of research indicates that there are four code mixings in the texts of Japan songs in Can’t Buy My Love Album. These four code mixings represent the form of code mixings which are the insertion of words, phrases, word replicates, and clauses. The type of song texts in Can’t Buy My Love Album is the external type of code mixing. There three functions of communication in Can’t Buy My Love Album, which are social communication, expressive communication and instrumental communication. The author suggests that other student shall carry out further research with the wider data source to obtain more variable results.   Keywords: Language, Language Variation, Code Shift, Code Mixing